Los futuros de la memoria en América Latina : Sujetos, políticas y epistemologías en disputa - Blanco, Fernando A.; Lazzara, Michael J., 1975- (Book collections on Project MUSE., 2022)
"This book points out and examines the paradigm shift experienced in recent years by the field of memory studies: an intersectional and epistemological turn that spatially, temporally and ideologically displaces the immediate (testimonial) and mediate (transgenerational) reflection of retrospective symbolization of the repressive processes that occurred during the Latin American civic-military dictatorships, proposing to work beyond the equation 'victim-perpetrator-witness'. The field is reinvigorated thanks to the re-signification of violence not as an effect but as a foundation, a phenomenon of a structural nature associated with the collapse of the democratic state in the region, accompanied in several cases by the return to power of the right wing through 'soft coups' sustained by the narrative of 'capitalist common sense'. This second neoliberal phase materializes in sustained systemic violence against communities and actors (racial, ethnic, sexual, gender and class) who are displaced, precarious, persecuted or decimated for their community resistance to the economic regime that marginalizes them. Their emancipatory narratives and practices are the focus of this book and the basis for the epistemological and intersectional turn in memory studies that the book addresses"--